Propaganda on the Stage: the Theater of Social Protest in France between the 19th and 20th Centuries - Kaczmarek, Tomasz (Populismo y propaganda: entre el presente y el pasado, 2020)
The author of the article presents the main characteristics of the theater of social protest in France, which enjoyed an indisputable esteem for three decades before the First World War. Anticipating the event of agitprop, that theater, intentionally neglected for almost a century, resorted to various forms of propaganda which aimed to win the favor with the public, a victim of the unfair capitalist system. At first glance, the goal of the anarchist authors was to open the eyes of the poor to the injustices of the bourgeois order and then to incite them to social protest. The dissemination of libertarian concepts was done through naturalist and feminist plays, melodramas and farces which approximated the old tradition of popular theater.